A slope deformation measurement method based on laser datum and complex target motion model. (August 2022) - Wang, Huifeng; Cheng, Haoyi; Jiao, Yunmei; Huang, He; Wu, Zejian; Song, Shangzhen; Wen, Limin; Huan, Yufei
Highlights: Automatic monitoring of slop stability using laser reference and inclination sensor. Complex target motion model considering translation, rotation and laser tilt. Using FPGA to realize gray-scale centroid method to extract light spot. Compensation and optimization of slope three-dimensional deformation calculation. Abstract: Highway slope stability analysis and monitoring is of great significance to ensure the safety of highway infrastructure. Based on the consideration of complex target motion model, a high-precision laser datum highway slope multi-dimensional deformation measurement method is proposed in this paper, which overcomes the problem of low measurement accuracy in traditional methods, and realizes high-precision real-time monitoring of highway slope stability. Firstly, the measurement principle and deformation data solution method combining the laser benchmark and the intelligent photoelectric imaging target are given. Then, considering the multi-dimensional complex motion of the photoelectric imaging target, a solution model of the multi-dimensional motion parameters of the measuring point considering the multi-dimensional complex motion vector of the target is deduced. Then, the inclination sensor is used as the measurement method of the multi-dimensional inclination of the target, combined with the high-precision processing algorithm of target spot center based on image processing, the high-precision measurement of multi-dimensional deformation of target plane is realized; Finally, the prototype of the measurement system is built and compared in the laboratory, and the actual highway slope is measured and verified in the outfield. The experimental results show that the measurement error considering the complex target movement is less than 0.25 mm, which is greatly improved compared with the traditional method, and meets the needs of high-precision slope relative deformation measurement.